1983
DOI: 10.1177/001440298305000103
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research on Parents and Families of Gifted Children

Abstract: This article focuses on research and issues dealing with parents and families of gifted children. Although the importance of parents is seen as a key factor in the development of all children, discussion of the role of parents with their gifted children has been superficially treated. Many articles deal only with general rules of thumb about good parenting. In order to avoid this, the present article begins with an extensive review and synthesis of research in the area of parents and families of gifted youngst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 19 publications
1
36
0
2
Order By: Relevance
“…Research in other areas presents the relationship between high ability and peer influence as problematic (Colangelo and Dettermann, 1983;Winner, 1996). There is some evidence that the possession of a gift or talent can endanger social acceptance, and this seems to be especially the case for girls (Luftig and Nichols, 1991;Winner, 1996).…”
Section: Environmental Characteristicsmentioning
confidence: 99%
“…Research in other areas presents the relationship between high ability and peer influence as problematic (Colangelo and Dettermann, 1983;Winner, 1996). There is some evidence that the possession of a gift or talent can endanger social acceptance, and this seems to be especially the case for girls (Luftig and Nichols, 1991;Winner, 1996).…”
Section: Environmental Characteristicsmentioning
confidence: 99%
“…A great many positive factors include acceptance, support, and independence training. Negative factors, documented particularly for those attaining creative distinction, include evidence of emotional distance and "apartness" of family members, marital instability, and conflict (e.g., Albert & Runco, 1986;Colangelo & Dettmann 1983;Davenport, ZahnWaxler, Adland, 8c Mansfield, 1984;Dewing, 1970;Goertzel & Goertzel, 1962;Richards, 1981). In fact, in their study of eminent 20th century individuals, the Goertzels (1962) found that 85% came from markedly troubled homes.…”
Section: Creativity Research Journalmentioning
confidence: 99%
“…The "Guidance needs" section consisted of a total of 39 five-point Likert-type items with four sub-dimensions (Academic, Social, Psychological and Opportunities Provided by the Family), which was written on the basis of the relevant literature [6,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]33]. The option of the open-ended "other" was also added to the end of these items.…”
Section: Data Gathering Instrumentmentioning
confidence: 99%